Positioning context front and center in international human resource management research. (17th November 2022) - Farndale, Elaine; Bonache, Jaime; McDonnell, Anthony; Kwon, Bora
Abstract: The international human resource management (IHRM) field naturally lends itself to spotlighting the importance of internal and external organizational contexts to help understand how to manage employees in organizations effectively. However, we argue that the range of opportunities that the field creates to understand this context has not yet been fully embraced by IHRM scholars. To address this gap, this special issue explores: (a) the variety of approaches to theorizing how contexts promote or constrain organizational practice; and (b) relevant methodologies that might allow us to unearth novel context‐dependent theory in international HRM. We propose a distinction between variable‐oriented theorizing (that explains the effects of internal and external contexts on the phenomena under study) and context‐dependent theorizing (that requires researchers become intimately familiar with the setting under study to understand context as a shaper of meaning). This editorial also highlights how the articles in the special issue contribute to stimulating further context‐dependent IHRM research.